Usefulness of the procalcitonin test in young febrile infants between 1 and 3 months of age - In Sul Lee; Young Jin Park; Mi Hyeon Jin; Ji Young Park; Hae Jeong Lee; Sung Hoon Kim; Ju Suk Lee; Cheol Hong Kim; Young Don Kim; Jun Hwa Lee (Korean Pediatric Society, 2018)
Purpose To study the usefulness of the procalcitonin (PCT) test in young febrile infants between 1 and 3 months of age. Methods We evaluated the medical records of 336 febrile infants between 1 and 3 months of age who visited the Emergency Department or outpatient department of Samsung Changwon Hospital from May 2015 to February 2017, and analyzed the clinical characteristics between infants in the serious bacterial infection (SBI) group and non-SBI group. Results Among the 336 infants, 38 (11.3%) had definitive SBI (bacteremia, n=3; meningitis, n=1; urinary tract infection, n=34). The mean PCT (6.4±11.9 ng/mL) and C-reactive protein (CRP) level (3.8±2.6 mg/dL), and the absolute neutrophil count (ANC) (6,984±4,675) for patients in the SBI group were significantly higher than those for patients in the non-SBI group (PCT, 0.3±1.2 ng/mL; CRP, 1.3±1.6 mg/dL; ANC, 4,888±3,661). PCT had lower sensitivity (43.6%), but higher specificity (92.6%) and accuracy (86.9%) than CRP (92.3%, 25.3%, and 33.0%) for identifying SBI. The area under the receiver operating characteristic curves (AUCs) for definitive SBI were PCT 77.0%, CRP 80.8%, WBC 56.8%, ANC 67.8%, and PLT 48.1%. The AUCs for definitive SBI were PCT+CRP 85.4%, PCT+WBC 77.2%, PCT+ANC 81.3%, CRP+WBC 80.1%, and CRP+ANC 81.6%. Conclusion Our results suggest that the PCT test or a combination of PCT and CRP tests is a more accurate and specific biomarker to detect and rule out SBIs.